2022
DOI: 10.23887/jpbi.v10i1.49840
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Teaching English Using Differentiated Instruction in Senior High School during Covid-19 Pandemic

Abstract: A large number of teachers are adopting one-size-fits-all teaching instruction for all students. However, the diversity of student characteristics should require teaching strategies that can meet various mixed abilities in the classroom. The study focused on analyzing the implementation of differentiated instruction and investigating the challenges encountered by the teacher in implementing differentiated instruction in teaching during the pandemic of Covid-19 in Senior High School. This research uses a descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The research showed us that students in the differentiated group were motivated to complete their work more frequently than students in the non-differentiated. While Nyoman (2022), Halim (2022), andMirawati et.al. (2021) held some research on DI used in English class.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The research showed us that students in the differentiated group were motivated to complete their work more frequently than students in the non-differentiated. While Nyoman (2022), Halim (2022), andMirawati et.al. (2021) held some research on DI used in English class.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Besides, research underscores the significance of differentiated instruction in enhancing learning experiences. For instance, Satyarini (2022) observed the partial Implementation of differentiated instruction in ESL teaching in a senior high school. The study highlighted the teacher's efforts to accommodate students' varied learning profiles by utilizing diverse media and instructional strategies, including PowerPoint presentations, videos, and graphic organizers, to facilitate access to content and personalize the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Their research, involving first-year EFL students, identified positive attitudes towards adaptive instructional methods that offer learning materials and activity choices and group students according to their preferences. In Indonesia, Nyoman et al (2022) examined the challenges of applying differentiated instruction during the COVID-19 pandemic. Their findings revealed only partial Implementation, with efforts to adapt materials, methods, and products to cater to students' interests and learning profiles.…”
Section: Introductionmentioning
confidence: 99%
“…This preliminary investigation led the researchers to conduct further investigations on learning practices, especially on instruction. Regular evaluation of instruction and its efficacy is necessary for improving teaching and learning techniques (Pande Nyoman et al, 2022), as designing instruction is considered the most significant challenge in implementing the new teaching model. Moreover, with the learner-centered paradigm of education and training (Reigeluth et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with the learner-centered paradigm of education and training (Reigeluth et al, 2016). In this context, learning instruction is the purposeful direction of the learning process, which becomes one of the significant teacher class activities along with planning and management of offline and online learning instruction (Pande Nyoman et al, 2022). It is one core factor for a teacher to create interactive Learning, which improves students' participation and performance for 21st-century learners.…”
Section: Introductionmentioning
confidence: 99%